The Influence of Digital Marketing on Customer Decisions to Use Brimo Services at Bank Rakyat Indonesia - Fadly Rezeki,; Aulia Indra,; Meisa Fitri Nasution, (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to determine the influence of digital marketing on customer decisions to use Brimo services at Bank Rakyat Indonesia. The sample size was 96 respondents. This study used validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t-tests, F-tests, and coefficients of determination using SPSS. The study was conducted to examine how independent variables influence dependent variables and the percentage level of influence of research variables by distributing research questionnaires to respondents and conducting testing. The results of the study show that all independent variables have an influence on the dependent variable with all t count values ​​> t table and significant values ​​<0.05, user reviews have a positive and significant effect on customer decisions (4.784>1.985), product comparisons have a positive and significant effect on customer decisions (2.343>1.985) and content marketing has a positive and significant effect on customer decisions (3.506>1.985), the simultaneous test value is 50.443>3.09 all independent variables have an effect on the dependent variable with a determination level of 0.510 or 51.00% giving a positive and significant effect.